The Growth, Fruit Set and Fruit Cracking Incidents of Tomato Under Shade - Ulinnuha, Zulfa; Chozin, Muhammad Achmad; Santosa, Edi (Department of Agronomy and Horticulture, IPB University, 2020)
Six tomato genotypes were grown in the field under full sun at 50% reduced light intensity using shading net to evaluate growth, fruit set, and fruit cracking incident. The experiment was conducted during the rainy season in December 2016 to March 2017 in Cikarawang Experimental Station, Bogor, Indonesia. The genotypes tested were sensitive (“Tora” and F7005001-4-1-12-5), tolerant (F7003008-1-12-10-3 and F7003008-1-12-16-2), and shade-loving (SSH-3 and “Apel Belgia”). The results showed 50% shading delayed flowering and harvesting time in all genotypes. Genotype and shading treatments had an independent effect on fruit set. Shaded plants had lower flower abortion and resulted in a higher number of fruits per harvest, except in “Apel Belgia” and “Tora” genotypes. Fruit cracking incidents were low under shading implying the use of shading can increase tomato quality. However, it needs further investigation through using natural shading, e.g., intercropping system before this finding is applied in farmers’ field.